Low-altitude rocket stability under various fin cant angles and cross wind speeds / Zuraidah Salleh ... [et al.] - Salleh, Zuraidah; Mohd Asy’ari, Umi Alya Farhani; Abdul Hamid, Ahmad Hussein; Muhammad, Mohamad Amirul; Abdul Ghaffar, Zulkifli (UiTM Press, 2025)
This paper undertakes a comprehensive aerodynamic analysis of lowaltitude rockets. The stability of rockets launched from low-latitude regions presents unique challenges, such as the presence of trade winds and localised turbulence, which may potentially lead to deviations from the intended flight path and an increased risk of structural failure. The study focuses on the R3KM rocket and investigates two distinct configurations: a three-fin rocket canted at 0°, 2.5°, and 5°, as well as a four-fin rocket canted at the same angles. To assess the rocket's stability during flight, numerous simulations have been conducted across a variety of wind velocities. Concurrently, the dynamic stability analysis focuses on the rocket's ability to respond effectively to external disturbances such as crosswind. Significant emphasis is placed on refining the fin design to optimise both aerodynamic efficiency and stability. The use of OpenRocket software allows for simulations, guiding the iterative process of improving the rocket's aerodynamic configuration. The findings from this study indicate that canted fins enhance the rocket's stability as wind speeds increase. The three-fin R3KM configuration attains greater apogees at about 5%, however, the four-fin version exhibits enhanced aerodynamic stability at elevated wind speeds (i.e., 2 m/s to 4 m/s higher critical wind speed), depending upon the cant angle. These results suggest that while the three-fin design may reach greater heights, the four-fin design provides better stability in challenging wind conditions. This study's findings are anticipated to enhance the efficiency and reliability of rockets, thereby advancing the field of rocket aerodynamics.